Study to Quantitative Impact of Climate Change and Human Activities on Runoff in the Upper Reaches of Nanpan River - GU Guihua; LI Xuehui; YU Shoulong; DUAN Lusong (Renmin Zhujiang)
According to the runoff and precipitation of Jiangbianjie Hydrographic Station and 20 precipitation stations in Nanpan River from 1956 to 2016, this paper analyzes the change characteristics of precipitation and runoff and the change points of runoff series, divides the series into three analysis periods such as 1956—1973, 1974—2001 and 2002—2016 on the basis of the change characteristics of runoff, and conducts the quantitative analysis for the contribution rate of climate change and human activities to the runoff change of Nanpan River Basin by the separation judgment method, with 1956 to 1973 as the reference period. The results show that:(1) Precipitation is the main source of runoff, and the average water yield coefficient for many years is 0.24. The precipitation atupper reaches of Jiangbianjie Hydrological Station showed a non-significant decrease trend, but the runoff showed an significant decrease trend. (2) From 1974 to 2001, the contribution rates of climate change and human activities to runoff change were 65.9% and 34.1% respectively. From 2002 to 2016, those were 82.8% and 17.2% respectively, so the climate change was the main factor affecting runoff change. (3) During the analysis periods from 1974 to 2001 and 2002 to 2016, the annual distribution of runoff is mainly reflected in the homogenization of monthly runoff and the planarization of peak value, and human activities are the main factors affecting monthly runoff. It can be seen that the climate change is still the main contributory factor for runoff change, but the impact of human activities on runoff are increased.